Student's impressions on the physical appearance of female teachers some perceived effects on respect, discipline and learning behavior - Viray, Firma Caccam; Ynchausti, Natividad S. (1987)
The objectives of the study were 1) to determine the types of impressions formed by students on their teachers' physical appearance; and 2) to determine the implication of these impressions on teaching-learning behavior and student-teacher relationship in the classroom. Corollary to the above objectives, the study attempted to seek answers to the following problems: what impressions are formed by students on their teachers' physical appearance with regards to type of clothing, posture and carriage, grooming practices, hairstyles, shoes and accessories; is there a relationship between the impressions formed by students and their sex and age?; what aspects of teachers' physical appearance do students generally like?; and what types of clothing relate to teachers' capability to command respect, instill discipline, and create positive learning behavior in students? The study was conducted at the Central Luzon State University (CLSU), Munoz, Nueva Ecija. The respondents included 467 second and fourth year students of which 168 were males and 268 were females. A checklist questionnaire was uses for obtaining data. The questionnaire consisted of the background information of the respondents, impressions on the different aspect of teachers' appearance, and student's perception of different styles in relation to respect, discipline and positive learning behavior. The analysis of the data yielded the following results: sex and age of the respondents are not related to impressions of teachers' physical appearance. In general, the students surveyed prefer teachers in uniform. This type of attire is perceived to relate to better respect, discipline, and positive behavior. T-shirts worn with denim pants was perceived by the students to be negatively related to respect, discipline, and positive learning behavior. An analysis of variance on the different age groups indicated that perceptions of clothing styles change with increasing age. As a person becomes older, his perceptions perceptions become become more objective. The findings of the study suggest some recommendations for educators and school administrators in the formulation of specific guidelines for a code of dress for academic staff. The study also suggest further improvements used and methods of gathering data in doing similar study. Moreover, a similar study can be conducted involving variables such as socio-economic background, educational background, religious affiliation, and geographical location, aside from sex and age variables.
Thesis (M. A. Home Economics)--University of the Philippines, Diliman.
Keywords: Physical-appearance-based bias -- Philippines -- Munoz (Nueva Ecija).; Teacher-student relationships -- Philippines -- Munoz (Nueva Ecija).